2021
DOI: 10.1007/s11357-021-00354-w
|View full text |Cite
|
Sign up to set email alerts
|

In vivo proton magnetic resonance spectroscopy detection of metabolite abnormalities in aged Tat-transgenic mouse brain

Abstract: Most individuals living with HIV in the USA are over 45 years old and are vulnerable to the combined effects of HIV and aging. Antiretroviral therapies reduce HIV morbidity and mortality but do not prevent HIV trans-activator of transcription (Tat) protein expression or development of HIV-associated neurocognitive disorder (HAND), which may be caused by Tat. Tattransgenic (Tat-tg) mice are used to study Tat's effects, typically after transgene induction with doxycycline. However, uninduced Tat-tg mice experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…Briefly, mice expressed the Tat 1-86 protein via conditional, GFAP-relegated expression under regulation of a reverse tetracycline-controlled transactivating (rtTA) transcription factor. We and others have previously confirmed mRNA expression of tat in the brain and spinal cord of these mice [44][45][46] and include confirmation in the present tissues via quantitative real-time PCR (see Supplemental Data, Figure S1). Tat(−) control mice lacked the tat transgene but did express the rtTA transcription factor [47].…”
Section: Introductionsupporting
confidence: 80%
“…Briefly, mice expressed the Tat 1-86 protein via conditional, GFAP-relegated expression under regulation of a reverse tetracycline-controlled transactivating (rtTA) transcription factor. We and others have previously confirmed mRNA expression of tat in the brain and spinal cord of these mice [44][45][46] and include confirmation in the present tissues via quantitative real-time PCR (see Supplemental Data, Figure S1). Tat(−) control mice lacked the tat transgene but did express the rtTA transcription factor [47].…”
Section: Introductionsupporting
confidence: 80%
“…Together, these data support the notion that maintaining the endocrine milieu of the CNS promotes resilience to neurodegenerative insults, including those associated with older age. In support, we recently found that T declines with age in the medial prefrontal cortex and striatum of Tat-expressing transgenic mice, concurrent with decrements in excitatory and inhibitory neurotransmitters as well as endogenous antioxidants detected with magnetic resonance spectroscopy [ 89 ]. These findings are consistent with clinical observations of cognitive impairment [ 90 ] that occurred in parallel with cerebral metabolic disturbances including a reduction of N-acetyl aspartate and an increase of choline and myoinositol, markers of inflammation, in HIV + patients [ 29 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 77%
“…In this study, the serum testosterone level of the male CHH group was lower than the male control group, and the serum estradiol level of the female CHH group was higher than the female control group, which was consistent with the previous reports ( Liu et al, 2020 ; Pooja et al, 2020 ). Estrogen has antioxidant ( Yazğan et al, 2016 ; Paris et al, 2021 ), anti-inflammatory ( Fallarino et al, 2010 ; Siani et al, 2017 ), and neuroprotective effects ( Cipolla et al, 2009 ; Robison et al, 2019 ), which was been widely reported. Although it has been reported in recent years that androgens also have anti-inflammatory ( Mohamad et al, 2019 ; Babcock et al, 2022 ) and antioxidant ( Ahlbom et al, 2001 ) effects, however, the protective effect of testosterone has a dichotomous effect.…”
Section: Discussionmentioning
confidence: 99%